Principal leadership as a moderator: Enhancing the impact of work environment and motivation on teacher performance - Pradika, Rizka Ardhi; Rosidah; Perez, Liann Camille Davalos (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
This study aims to examine the effect of principal leadership as a moderating variable in the relationship between work environment, teacher's motivation, and teacher performance in Economics at high schools in Yogyakarta City. The method used is a quantitative approach with data analysis employing Structural Equation Modeling (SEM) through SmartPLS 4. The subjects of the study consist of 54 Economics teachers selected using purposive sampling. The instrument used is a structured questionnaire measuring four main constructs: teacher performance, principal leadership, work environment, and teacher's motivation. Data were collected from February to November 2024. Data analysis was conducted using SEM with the Partial Least Squares (PLS) approach. The results show that work environment and teacher's motivation positively affect teacher performance, with principal leadership acting as a moderator, although the moderating effect was not statistically significant at the 95% confidence level on some variables. These findings emphasize the importance of a supportive work environment, high teacher's motivation, and effective leadership in improving teacher performance.